2008
DOI: 10.2172/940753
|View full text |Cite
|
Sign up to set email alerts
|

300 Area Treatability Test: Laboratory Development of Polyphosphate Remediation Technology for In Situ Treatment of Uranium Contamination in the Vadose Zone and Capillary Fringe

Abstract: SummaryThe Hanford Site is a former nuclear defense production facility. A groundwater plume containing uranium, originating from a combination of purposeful discharges of wastewater to cribs, trenches, and ponds, along with some accidental leaks and spills related to nuclear fuel fabrication activities, has persisted beneath the Hanford Site 300 Area for many years. Despite the cessation of uranium releases and the removal of shallow vadose zone source materials, the remedial action objective to lower the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 197 publications
0
11
0
Order By: Relevance
“…In addition to those noted in previous publications (Wellman et al 2007(Wellman et al , 2008a(Wellman et al , 2011Bovaird et al 2010;Vermeul et al 2009), some limitations of polyphosphate treatment technologies were identified, which impact field scale applicability in different treatment zones. The trend of increased sedimentphosphate contact time resulting in higher phosphate precipitate (and a greater decrease in uranium leaching) implies that polyphosphate injection into groundwater may not deposit sufficient phosphate precipitate due to high groundwater flow (i.e., insufficient contact time).…”
Section: Conclusion and Challengesmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition to those noted in previous publications (Wellman et al 2007(Wellman et al , 2008a(Wellman et al , 2011Bovaird et al 2010;Vermeul et al 2009), some limitations of polyphosphate treatment technologies were identified, which impact field scale applicability in different treatment zones. The trend of increased sedimentphosphate contact time resulting in higher phosphate precipitate (and a greater decrease in uranium leaching) implies that polyphosphate injection into groundwater may not deposit sufficient phosphate precipitate due to high groundwater flow (i.e., insufficient contact time).…”
Section: Conclusion and Challengesmentioning
confidence: 74%
“…It is hypothesized that due to the slowly changing phosphate precipitates that form, uranium leaching will unlikely decrease during initial treatment, but over months to years, lower solubility hydroxyapatite can form coating uranium surface phases (i.e., uranium-carbonates, sodium-boltwoodite) or uranium phosphate phases may also form. Previous research demonstrated that under high bicarbonate conditions, autunite does not form, but uranium phosphate precipitates do form (Wellman et al 2008a Aqueous uranium leached from the phosphate-treated sediment columns over hundreds to thousands of hours generally shows decreased uranium mass leaching out and decrease in uranium release rate from phosphate-treated sediment compared with untreated sediment. During continuous groundwater or river flow for phosphate-treated sediments, column effluent uranium was 1 to 10 µg/L, compared to 5 to 12 µg/L for untreated sediments at exactly the same flow rate.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Injection of sodium phosphate is potentially the best reactant (Table 2.1), as the formation of autunite will likely immobilize uranium from further advection. The use of sodium phosphate (with and without tripolyphosphate [Wellman et al 2008a]) has been tested at low water content. Unknowns associated with this technology include the distribution of phosphate mass that would result from 99% gas/1% water injection.…”
Section: Selection Of Technologies For Laboratory Testingmentioning
confidence: 99%